PERSPEKTIF PEMILIHAN KEPALA DAERAH TAHUN 2029 - Eko Wahyono (LPPM STAI Muhammadiyah Probolinggo, 2025)
The regional head election as a form of democracy, to elect governors, mayors/regents, is always accompanied by problems and negative impacts, while in the regional head election system there are two methods of election: direct regional head elections and indirect regional head elections. This results in a model or idea that is no longer directly elected, reverting to the representative method that is identical to the period before the reform. The purpose of this research is to understand how direct regional head elections work and how indirect regional head elections are conducted. The research method used is normative research (library research) or literature review related to legislation. The results of this research indicate that direct local elections have caused various issues, thus it is necessary to reorganize the mechanisms, improve the regulations, and ensure the implementation of local elections that are honest, open, and fair. Representative local elections do not contradict the 1945 Constitution in Article 18 Paragraph (4), where local leaders are chosen democratically, hence representative local elections can reduce these problems.